From 'opportunity' to 'insecurity': the psychological contract of highly skilled immigrants in Western Australia. (2nd July 2016) - Casado, Renata; Caspersz, Donella
ABSTRACT: The aim of this paper is to develop a conceptual framework and provide empirical support from a study that has explored the lived employment experience of highly skilled immigrants (HSIs) in Western Australia (WA), and how this experience influences their decision to remain or leave the WA labour market. To provide this analysis, we ask how the wider context has affected the psychological contract (PC) of HSIs. A qualitative longitudinal research (QLR) case-study design that draws on three phases of semi-structured in-depth interviews with participants ( n = 26) that was conducted between 2010 and 2014 informs the discussion. We contribute to the employment relations and PC literature by highlighting the influence of context in understanding the PC; and to labour migration literature by providing an understanding of HSIs' work experiences.